2014
DOI: 10.3892/mmr.2014.2380
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin analogues with high activity for inhibiting human prostate cancer cell growth and androgen receptor activation

Abstract: The androgen receptor (AR) has a critical role in prostate cancer development and progression. Several curcumin analogues (A10, B10, C10, E10 and F10) with different linker groups were investigated for their effects in human prostate cancer CWR‑22Rv1 and LNCaP cell lines. The ability of these compounds to inhibit testosterone (TT)‑ or dihydrotestosterone (DHT)‑induced AR activity was determined by an AR‑linked luciferase assay and by TT‑ or DHT‑induced expression of prostate specific antigen. Compounds F10 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
(32 reference statements)
0
33
0
3
Order By: Relevance
“…Similarly, a herbal formulation from Ecuador, BIRM effectively suppressed AR signaling in AR + (LAPC‐4 and LNCaP) cell lines and orthotopic models of CaP . Studies suggested that curcumin analogs suppress DHT‐induced AR activation in AR + CaP cells …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a herbal formulation from Ecuador, BIRM effectively suppressed AR signaling in AR + (LAPC‐4 and LNCaP) cell lines and orthotopic models of CaP . Studies suggested that curcumin analogs suppress DHT‐induced AR activation in AR + CaP cells …”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial also demonstrated that a curcumin dose of 8 g per day when taken with Gemcitabine is safe and well tolerated as a supplement 7 . Other studies have demonstrated similar effects of curcumin and Docetaxel for ovarian cancer, 33 as well as curcumin and oxaliplatin for colon cancer 33, 37. Studies investigating the use of Docetaxel and curcumin as potential treatments for breast cancer have also shown that curcumin can be well tolerated in addition to the chemotherapy 36 …”
Section: Curcumin and Cancer Treatmentmentioning
confidence: 99%
“…The bioactive compound curcumin, derived from turmeric ( Curcuma longa ) has received considerable attention due to its anti-carcinogenic activities as demonstrated in numerous studies in animal models [4347]. Importantly, several curcumin analogs have been shown to function as AR antagonists in the presence of AR and the AR co-activator, ARA70 [48].…”
Section: Natural Products Against Pcamentioning
confidence: 99%
“…Unfortunately, the oral bioavailability of curcumin is low and making improvements to this is currently an active area of research [3]. Several investigators demonstrated that curcumin analogs inhibit testosterone- or DHT-induced AR activity and inhibit growth of CWR-22Rv1 and LNCaP cells [43, 49]. …”
Section: Natural Products Against Pcamentioning
confidence: 99%